Inscription on a Roman Stylus from London - Keyer, Denis (Hyperboreus, 2019)
I interpret the metric inscription on the stylus from the Bloomberg excavations in London (Tomlin 2018a, 5–6) as a polymetron that consists of two iambic senarii and an elegiac distich. In acul[eat]um, if this restoration is correct, -ea- must be scanned monosyllabically with synizesis. In lines 2–3 I punctuate before ut and after rogo, so that the ut clause depends on rogo. In line 4 I restore ut[i], which provides a hexameter: si fortuna daret quo possem largius uti! (si introduces a wish, like utinam). In the word that follows via the third letter must be identiﬁed as N (not as V); I suggest to restore either cen[a] (the ablative that is asyndetically coordinated with via) or Cen[i] (the vocative of Cenius). In either case via must be scanned monosyllabically with synizesis.